2015
DOI: 10.1080/14786419.2015.1038998
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of carvacrol, rosmarinic, oleanolic and ursolic acid extraction from oregano herbs (Origanum onites L., Origanum vulgare spp. hirtum and Origanum vulgare L.)

Abstract: The aim of our study was to increase the extraction efficiency of carvacrol, rosmarinic, oleanolic and ursolic acid from the different species of oregano herbs (Origanum onites L., Origanum vulgare spp. hirtum and Origanum vulgare L.). Various extraction methods (ultrasound-assisted, heat-reflux, continuous stirring, maceration, percolation) and extraction conditions (different solvent, material:solvent ratio, extraction temperature, extraction time) were used, and the active substances were determined by HPLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 8 publications
2
28
0
Order By: Relevance
“…As the carvacrol content is high (75.70%) in our sample (Table S1), the current O. onites sample is considered as carvacrol-type. In the recent study, Baranauskaitė et al (2016) reported that carvacrol content found depended on the oregano species and the extraction methods.…”
Section: Resultsmentioning
confidence: 99%
“…As the carvacrol content is high (75.70%) in our sample (Table S1), the current O. onites sample is considered as carvacrol-type. In the recent study, Baranauskaitė et al (2016) reported that carvacrol content found depended on the oregano species and the extraction methods.…”
Section: Resultsmentioning
confidence: 99%
“…Prepared extract was filtered using vacuum filter. These conditions were determined in our previous study as the best for the extraction of main active compounds of Turkish Oregano [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The linear calibration curve was made and expressed by the following quadratic equation: R 2 (RA) = 0.999918, ( y = 2.01 · 10 7 x + 5.52 · 10 3 ), the linearity range: 10–100 μ g/ml. ( Figure 1(a) ) [ 18 ]. For determination of CA: the mobile phase was composed of methanol and water (60/40, v/v).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many extraction methods, all conventional, such as Soxhlet extraction [13], maceration [14], reflux extraction [15] and modern, e.g., ultrasonic-assisted extraction (UAE) [16], accelerated solvent extraction (ASE) and microwave-assisted extraction (MAE) [9] have been used to extract triterpenes and their derivatives from plant material. However, conventional organic solvent extractions have an energy-consuming nature, low extraction selectivity, lengthy extraction procedures, and cause environmental problems.…”
Section: Introductionmentioning
confidence: 99%